Macrophage Reprogramming with Anti‐miR223‐Loaded Artificial Protocells Enhances In Vivo Cancer Therapeutic Potential. Issue 35 (31st October 2022) - López‐Cuevas, Paco; Xu, Can; Severn, Charlotte E.; Oates, Tiah C. L.; Cross, Stephen J.; Toye, Ashley M.; Mann, Stephen; Martin, Paul
Abstract: Several immune cell‐expressed miRNAs (miRs) are associated with altered prognostic outcome in cancer patients, suggesting that they may be potential targets for development of cancer therapies. Here, translucent zebrafish ( Danio rerio ) is utilized to demonstrate that genetic knockout or knockdown of one such miR, microRNA‐223 (miR223), globally or specifically in leukocytes, does indeed lead to reduced cancer progression. As a first step toward potential translation to a clinical therapy, a novel strategy is described for reprogramming neutrophils and macrophages utilizing miniature artificial protocells (PCs) to deliver anti‐miRs against the anti‐inflammatory miR223. Using genetic and live imaging approaches, it is shown that phagocytic uptake of anti‐miR223‐loaded PCs by leukocytes in zebrafish (and by human macrophages in vitro) effectively prolongs their pro‐inflammatory state by blocking the suppression of pro‐inflammatory cytokines, which, in turn, drives altered immune cell‐cancer cell interactions and ultimately leads to a reduced cancer burden by driving reduced proliferation and increased cell death of tumor cells. This PC cargo delivery strategy for reprogramming leukocytes toward beneficial phenotypes has implications also for treating other systemic or local immune‐mediated pathologies. Abstract : Leukocytes have remarkable cancer surveillance capacities and so reprogramming them away from cancer nurturing and toward cancer killing is a therapeutic aspiration. This study reports how intravenous (or direct) injection of miniature artificial protocells loaded with anti‐microRNA‐223 cargo can reprogram cancer‐associated macrophages in larval and adult zebrafish leading them to be more pro‐inflammatory and thus able to drive melanoma shrinkage.